METHOD OF VERIFICATION OF STANDARD ANTHROPOMETRICAL SURVEYS FOR CLOTHING - SLAVINSKA, Alla; MYTSA, Viktoriia; ALBERTOVUCH, Viktoriia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The performed research of normative documents made it possible to quantify the technical conditions of anthropometric body measurements and to determine how the nomenclature of anthropometric measurements depends on the classification of clothing. The aim of the study was to develop a methodology for verifying anthropometric measurements of the human body, taking into account the functional characteristics of clothing. A criteria approach to the synchronization of verification means of standards identification of measurement names by measurement method and measurement classification groups (horizontal, vertical, others) was used. Validation of standard measurements for the ergonomic design of garments and harmonization of control measurement code designations in finished garments have been performed. Standard control measurements were interpreted into additional dynamic compliance measurements to take into account the level of deformation of parts during operation and to ensure freedom of movement. Technical regulation of the anthropometric information volume is confirmed by the equivalence of the optimization problems of the considered anthropometric standards in the form of the linear programming problem of the set of anthropometric measurements. The matrix of conditions for fixing anthropometric measurements in six regulatory documents was studied. It was established that the set pair 25 < 28 determines the technical conditions of quality control on the dummy of the finished product. Using basic and auxiliary reference measurements in the clothing size designation provides a flexible combination of chest, waist and hip measurements for women and chest and waist measurements for men. Consideration of the range of additional control vertical measurements is confirmed by calculating the indices of balance in the longitudinal direction of the female figure of size 164-96-104.
Keywords: anthropometric survey; regulatory documents; means of verification; control measurements; clothing size